14. About Aeonio-Euphorbion canariensis Sundíng 1972, correct alliance name against Kleinio-Euphorbion canariense Rivas Goday & Esteve 1965 - del Arco Aguilar, Marcelino (Lazaroa, 2014)
About Aeonio-Euphorbion canariensis Sundíng 1972, correct alliance name against Kleinio-Euphorbion canariense Rivas Goday & Esteve 1965